Program PUSAKA Sebagai Pemicu Perkembangan Kinerja Pengelolaan Lingkungan PT X - Risma Indah Salsabila (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
One of the government's efforts to protect the environment in the Indonesian industrial sector is by establishing laws and regulations that become a reference for the public and business actors and/or activities related to the environment. The government, through the Ministry of the Environment, issued regulations in the form of PROPER as an evaluation of industrial performance in environmental management. Based on the PROPER program mentioned above, the East Java Provincial Government is implementing the Environmental Trust Business/Activity Development Program or known as PUSAKA, which aims to provide environmental management guidelines based on environmental permits held by businesses and/activities (non-PROPER) in East Java. The PUSAKA mentoring program is used to prepare business actors and/or activities in East Java to achieve PROPER. Apart from that, it can also improve environmental management performance in business entities and/or activities in East Java Province, especially PT X. The PUSAKA development program has been successful in becoming a trigger for evaluating PT X's environmental management. Because it succeeded in increasing compliance with PPA and PLB3 by 85.7% and 3.75%.